The Relationship of Head of Room's Participative Leadership, Work Engagement, and Interpersonal Communication with Nurses' Job Satisfaction - Solehudin Solehudin; Inas Syabanasyah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Job satisfaction among nurses is an important indicator of healthcare service quality and is influenced by various organizational and interpersonal factors. This study aims to analyze the relationship between the head nurse’s participative leadership, work engagement, and interpersonal communication with nurses’ job satisfaction in the inpatient units of a private hospital in Jakarta. A quantitative analytic correlational design was employed with a total sample of 214 nurses selected through proportional stratified random sampling. Data were collected using standardized and validated questionnaires measuring participative leadership, work engagement, interpersonal communication, and job satisfaction. The results of multivariate analysis using multiple logistic regression demonstrated that participative leadership (OR = 46.5; p = 0.01), work engagement (OR = 13.5; p = 0.04), and interpersonal communication (OR = 14.7; p = 0.03) significantly influenced nurse job satisfaction. Nurses who perceived good participative leadership, high engagement, and effective interpersonal communication were significantly more likely to report job satisfaction. These findings highlight the importance of strengthening participative leadership practices, fostering engagement, and enhancing interpersonal communication to improve job satisfaction and support the creation of a conducive work environment in nursing units.